1, 2, 4‐Triazole‐conjugated 1, 3, 4‐thiadiazole hybrid scaffolds: A potent ameliorant of carrageenan‐induced inflammation by lessening proinflammatory mediators. Issue 1 (7th November 2019) - Pathak, Prateek; Shukla, Parjanya K.; Naumovich, Vladislav; Grishina, Maria; Verma, Amita; Potemkin, Vladimir
Abstract: Inflammation acts as an alarming signal for the progression of various biological complications. Various reports in the literature have revealed that heterocycle‐containing synthetic compounds have a restorative capability against acute and chronic inflammatory stages. In the current study, we synthesized a series of 1, 2, 4‐triazole‐conjugated 1, 3, 4‐thiadiazole hybrid scaffolds and evaluated their impacts against carrageenan‐induced paw edema and proinflammatory markers in Wistar rats. Further, 3D QSAR study (three‐dimensional quantitative structure–activity relationships), ADMET (absorption, distribution, metabolism, and excretion) profiling, and docking studies were performed to determine the possible mechanism of the action of the derivatives. The study shows that the most active derivatives, 13f and 13g, have optimal logP, a higher anti‐inflammatory activity score, and poor metabolism at various sites of cytochrome P450. The docking studies recommended that the synthesized compounds have a similar affinity as the ligands A307, 63X, and S58 to interact with tumor necrosis factor‐α, COX‐1, and COX‐2. So, these molecules will definitely hold a promise for the future drug development initiative. Abstract : A series of 1, 2, 4‐triazole‐conjugated 1, 3, 4‐thiadiazole hybrid scaffolds were synthesized and evaluated for their effects on carrageenan‐induced paw edema and proinflammatory markers in Wistar rats. The possible mechanism of action of the derivatives was studied. Docking studies revealed that the new compounds have a similar affinity as the ligands A307, 63X, and S58 to interact with tumor necrosis factor‐α, COX‐1, and COX‐2, making these molecules promising candidates for future drug development